Comparison of homeless clinic attenders with and without psychotic illness. (February 2020) - Nielssen, Olav; Jones, Naidene; Foung, Hayden; Nielssen, Amelia; Staples, Lauren; Large, Matthew
Aim: To compare the characteristics of clinic attenders in inner city homeless hostels with and without a diagnosed psychotic illness. Method: A cross-sectional study of homeless people attending psychiatric clinics in three inner city homeless hostels over a period of 8 years. The demographic characteristics, comorbid conditions, pathway to homelessness and pattern of homelessness of clinic attenders with a diagnosis of psychosis were compared with those who were not known to have psychotic illness. Results: 2389 homeless people attended one or more of the clinics in the 8 years of the study, of whom 1222 (51.2%) had a diagnosed psychotic illness, mostly schizophrenia. Those with psychosis were less likely to have been married (23.2% vs 45.5%), were less likely to have worked for more than a year (47.4% vs 74%) and were more likely to have been discharged from hospital to homelessness, to receive the Disability Support Pension (72.2% vs 38.3%), or be under financial management orders (12.0% vs 2.6%). Homeless people with psychosis were also more likely to have been homeless for more than a year, sleep in the open, and were less likely to have a current substance use disorder, problem gambling or a history of early life or recent trauma. A high proportion of those with psychosis (29.5%) had been released from prison to homelessness and a surprising number (22%) reported the loss of public housing tenancy. Conclusion: The results demonstrate the homeless with psychotic illness are particularly disabled and disadvantaged, often have multiple comorbid conditions, and many have been unable to maintain public housing tenancy. The inability of many of the homeless mentally ill to maintain public housing tenancy suggests the need for more supported housing to help the chronically homeless with psychotic illness maintain tenancy.